Respuesta :

Answer:

Option c is correct

Step-by-step explanation:

[tex]g(x) = \frac{x^2-6}{2x}[/tex]

We have to find g(n-5), for this purpose we will put x = n-5 in the above function

[tex]g(n-5) = \frac{(n-5)^2-6}{2(n-5)}[/tex]

[tex]g(n-5) = \frac{(n^2 + 25 - 10n - 6)}{10n-10}[/tex]

[tex]g(n-5) = \frac{(n^2 - 10n + 19)}{10n-10}[/tex]

Answer:

Choice C is correct answer.

Step-by-step explanation:

We have given a function.

g(x) = x²-6 / 2x

We have to find the value of g(n-5).

Replacing x with n-5 in given function, we have

g(n-5) = (n-5)²-6 / 2(n-5)

Using following formula

a²-2ab+b² = (a-b)(a-b)

n²-10n+25 = (n-5)(n-5)

g(n-5) = n²-10n+25-6 / 2n-10

Adding like terms , we have

g(n-5) = n²-10n+19 / 2n-10 which is the answer.

ACCESS MORE